Axial restraint Effects on Fire Resistance of Statically Indeterminate RC Beams - Cvetkovska, Meri; Lazarov, Ljupco; Todorov, Koce (Multi-Science Publishing, 2013)
The non uniform temperature fields in the cross section of the structural elements exposed to fire cause thermal dilatations which induce internal forces. In same time temperature changes cause longitudinal elongations and if these elongations are restricted, additional axial stresses will be induced. In this case the various support conditions can have a significant influence on fire resistance of reinforced concrete elements. In this paper three different support conditions as: pin-pin, pin-fixed and fully fixed were used to model RC beams with various level of axial restraint. The beams were exposed to the ISO-fire curve. The numerically obtained results are presented and based on these results it can be concluded that increasing of axial spring stiffness increases the induced axial forces and the fire resistance of the beams.
Keywords: RC beams, fire resistance, axial stifffness, nonlinear stress-strain analysis